The Reopening of Proceedings After the Judgment of the ECtHR in Cases Against Lithuania - Bruskina, Nika (Teisė, 2019)
The author of this article examines the case law of the Lithuanian courts of general jurisdiction and administrative courts related to the reopening of domestic criminal, civil, or administrative proceedings when the European Court of Human Rights (hereinafter – the ECtHR or the Court) finds a violation of the Convention for the Protection of Human Rights and Fundamental Freedoms and/or Protocols in the cases against Lithuania.
Keywords: the reopening of proceedings; the European Court of Human Rights; the Convention for the Protection of Human Rights and Fundamental Freedoms; case law; courts of general jurisdiction,; administrative courts